Strategies for Preserving Analog Collections in Digital Format as a Preventive Measure: A Systematic Literature Review - Khaddafi, Emir; Akbar, Audi (Indonesian Journal of Librarianship, 2024)
Background: Nowadays, various analog collections like cassettes, vinyl records, and VCDs circulate broadly within society. However, despite technological advancements, few institutions—whether governmental or private—have undertaken the task of digital preservation, even though the information contained within these collections holds significant value for future generations. The safeguarding of collections in analog formats, including cassettes, VCDs, and vinyl records, is essential due to the wealth of information they hold for future generations. Thus, preservation efforts are undertaken as a proactive strategy to ensure that the valuable content within these collections remains accessible for an extended period ahead. Purpose: To examine the transformation of analog collections into digital formats through preservation activities. Method: The method used in this study is the Systematic Literature Review (SLR). Results: The findings indicate that numerous organizations, encompassing both private and public sectors, have engaged in efforts to convert analog collections, including CDs, VCDs, and vinyl records, into digital formats. This awareness underscores the significance of these initiatives, ensuring that the information contained within the collections remains accessible for future use. Conclusion: The items typically safeguarded include video cassettes, audio recordings, and vinyl records, with the preservation method involving digitization or conversion of media functionalities. The most extensively maintained microfiche collections, as these collections continue to be utilized by the Indonesian populace. There remain individuals who engage in the preservation process by hand, yet gradually, they have begun to incorporate contemporary technology.